Antibacterial Property and Biocompatibility of Polypyrrole Films Treated by Oxygen Plasma Immersion Ion Implantation. Issue 8 (11th March 2020) - Li, Xiaoou; Qiu, Jiajun; Liu, Xuanyong
Abstract: Polypyrrole (PPy) films obtained by oxidative polymerization have positive charges in its main chains and therefore exhibit antibacterial properties to some extent. However, antibacterial activities of PPy films for biomedical applications are still insufficient. Here, to endow PPy films with excellent antibacterial properties and biocompatibility, oxygen plasma immersion ion implantation (O‐PIII) is performed to regulate their physicochemical properties, including but not limited to wettability and surface charge. Escherichia coli, Staphylococcus aureus, and MC3T3‐E1 cells are utilized to investigate the antibacterial properties and cytocompatibility, respectively. Results show that antibacterial property of PPy films against E. coli is enhanced after O‐PIII treatment, and it becomes more outstanding with the increase of implantation time, which may be ascribed to the improved hydrophilicity and change of sample surfaces from negatively charged to positively charged. The similar results cannot be found from S. aureus due to different cell membrane structure. Meanwhile, O‐PIII can significantly improve the biocompatibility of PPy films. Abstract : Oxygen plasma immersion ion implantation can regulate multiple physicochemical properties of polypyrrole films, including but not limited to wettability and surface charge, which are closely related to the antibacterial property and conduct surface cleaning of samples by the generated plasma. These functions can improve the antibacterial property against Escherichia coli and biocompatibility of polypyrrole films at the same time.